Integrating virtual reality into interactive learning media for improving science concept mastery in elementary education - Indah Desiana Putri; Munzil Munzil; Hari Wahyono; Sonny Soriano (JPP (Jurnal Pendidikan dan Pembelajaran), 2025)
This study aims to design and develop interactive learning media integrated with virtual reality (VR) technology to enhance elementary students’ conceptual understanding of science, particularly on the topic of the air cycle. The research employed the Lee and Owens (2004) model of instructional design, which includes analysis, design, development, implementation, and evaluation stages. The resulting product is a mobile learning application accessible via smartphones, featuring a user-friendly interface, multimedia content, learning videos, interactive simulations, and self-assessment quizzes. The VR-based learning environment allows students to explore scientific concepts both independently and collaboratively under teacher guidance, without spatial and temporal constraints. Expert validation involving media specialists, subject-matter experts, and science teachers indicated high levels of feasibility and appropriateness of the developed media. Field testing with fifth-grade students revealed a significant improvement in their conceptual understanding, as evidenced by increased post-test scores compared to pre-test results. These findings demonstrate that integrating VR into interactive learning media offers an effective approach to support science learning in elementary education and provides a promising direction for immersive digital pedagogy.